The Wnt pathway induces a naïve-like subpopulation in primed stem cells, while NME7AB leads to a homogeneous naïve-like population - Kevin R. Yi; Jac-Leen S.S. Nash; Mark G. Carter; Danica M. Walkley; Jiwon Jang; Benoit J. Smagghe; Andrew K. Stewart; Cynthia C. Bamdad (PLoS ONE, 2025)
The literature is replete with conflicting reports as to whether the Wnt/β-catenin pathway induces human stem cell differentiation or pluripotency. Recently, scientists showed that human stem cells expressing low levels of active β-catenin preferentially differentiate down a neuroectoderm lineage, whereas cells expressing high levels favor mesendoderm. However, these results appear to contradict two other studies, where researchers improved differentiation to both neuroectoderm and mesoderm by increasing levels of active β-catenin at the start of differentiation. Here, we show that stem cells cultured with naïve growth factor, NME7AB, express the highest levels of active β-catenin, yet readily differentiate into neuroectoderm and mesendoderm, without lineage preference. This raised the interesting question of whether activation of the Wnt/β-catenin pathway could itself play a role in maintaining or inducing a naïve-like state. The β-catenin agonist WNT3A was added to stem cells in the absence of any other growth factors, which induced the concurrent emergence of two segregated populations: an OCT4+, XaXa naïve-like population and an OCT4- population. This finding could explain the apparently inconsistent reports as to whether β-catenin induces pluripotency or differentiation, while raising additional questions. Notably, does the naïve-like sub-population, devoid of cell fate decisions, contribute to an increased differentiation potential? Conversely, are the OCT4- cells predisposed to differentiate more efficiently? To address these questions, we compared the differentiation of primed state stem cells, with or without pre-treatment with WNT3A, to that of naïve state stem cells. WNT3A pre-treatment improved the differentiation potential of primed stem cells, while having no effect in naïve stem cells. Furthermore, differentiation of the homogeneous population of naïve cells was superior to the primed state cells, even after WNT3A pre-treatment. This result is consistent with the idea that the improved differentiation is due to the sub-population of the WNT3A induced naïve-like cells.